PENGARUH WORD OF MOUTH, EXPERIENTIAL MARKETING DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN J.CO - Wulandari, Ketut Rai; Panasea, I Gede Nandya Oktora (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024DO - 10.24843/EEB.2024.v13.i06.p13, 2024)
Fast food restaurants have quite a big potential in Indonesia. One of the industries engaged in the fastfood restaurant sector in Denpasar City is J.CO Donuts & Coffee, a business pioneered by Johnny Andrean. Johnny Andrean creates donuts that have a perfect taste with a concept, shape and taste similar to donut outlets from the USA and prioritizes product quality by selecting quality basic ingredients. This study aims to examine and explain the influence of word of mouth, experiential marketing, and brand image on purchasing decisions among J.CO Donuts & Coffee Denpasar City consumers. This research was conducted in Denpasar City with a total sample of 160 respondents using a questionnaire using the Google form. Determination of the sample using a non-probability sampling model with purposive sampling technique. Data analysis technique using multiple linear regression analysis. The results of this study indicate that all hypotheses are accepted. Word of mouth has a positive and significant effect on purchasing decisions. Experiential marketing has a positive and significant effect on purchasing decisions. Brand image has a positive and significant effect on purchasing decisions.